Gut Microbiota From Sjögren syndrome Patients Causes Decreased T Regulatory Cells in the Lymphoid Organs and Desiccation-Induced Corneal Barrier Disruption in Mice - Schaefer, Laura; Trujillo-Vargas, Claudia M.; Midani, Firas S.; Pflugfelder, Stephen C.; Britton, Robert A.; de Paiva, Cintia S. (Frontiers in Medicine, 2022)
Sjögren Syndrome (SS) is an autoimmune inflammatory disorder characterized by secretory dysfunction in the eye and mouth; in the eye, this results in tear film instability, reduced tear production, and corneal barrier disruption. A growing number of studies show that homeostasis of the ocular surface is impacted by the intestinal microbiome, and several 16S sequencing studies have demonstrated dysbiosis of the intestinal microbiota in SS patients. In this study, we utilized metagenomic sequencing to perform a deeper analysis of the intestinal microbiome using stools collected from sex- and age-matched healthy (n = 20), dry eye (n = 4) and SS (n = 7) subjects. The observed Operational Taxonomic Units (OTUs) and Shannon alpha diversity were significantly decreased in SS compared to healthy controls, and there was a significant inverse correlation between observed OTUs and ocular severity score. We also identified specific bacterial strains that are differentially modulated in SS versus healthy subjects. To investigate if the differential composition of intestinal microbiome would have an impact on the immune and eye phenotype, we performed functional studies using germ-free mice colonized with human intestinal microbiota from SS patients and healthy controls. Flow cytometry analysis demonstrated reduced frequency of CD4+FOXP3+ cells in ocular draining cervical lymph nodes (CLN) in mice colonized with SS patient intestinal microbiota 4 weeks post-colonization. We also found that offspring of SS-humanized mice also have fewer CD4+FOXP3+ cells in the CLN as well as spleen, demonstrating vertical transmission. SS-humanized mice subjected to desiccating stress exhibited greater corneal barrier disruption as compared to healthy control humanized mice under the same conditions. Taken together, these data support the hypothesis that the intestinal microbiota can modulate ocular surface health, possibly by influencing development of CD4+FOXP3+ regulatory T cells (Tregs) in the ocular draining lymph nodes.